Local Storage Dynamics of Individual Wetlands Predict Wetlandscape Discharge. Issue 11 (28th October 2020) - Klammler, Harald; Quintero, Carlos J.; Jawitz, James W.; McLaughlin, Daniel L.; Cohen, Matthew J.
Abstract: Wetlands provide valuable hydrological, ecological, and biogeochemical functions, both alone and in combination with other elements comprising the wetlandscape. Understanding the processes and mechanisms that drive wetlandscape functions, as well as their sensitivity to natural and man‐made alterations, requires a sound physical understanding of wetland hydrodynamics. Here, we develop and apply a single reservoir hydrologic model to a low‐relief karst wetlandscape in southwest Florida (≈10 3  km 2 of Big Cypress National Preserve) using precipitation P and potential evapotranspiration PET as climatic drivers. This simple approach captures the dynamics of storage for individual wetlands across the entire wetlandscape and accurately predicts landscape discharge. Key model insights are the importance of depth‐dependent extinction of evapotranspiration ET and the negligible effects of depth‐dependent specific yield, the effects of which are diluted by landscape relief. We identify three phases of the wetlandscape hydrological regime: dry, wet‐stagnant, and wet‐flowing. The model allowed a simple steady‐state analysis, which demonstrated the sudden seasonal shift between wet‐stagnant and wet‐flowing states, indicating a consistent threshold at P  ≈  PET . Notably, stage data from any single wetland appears sufficient for accurate whole‐landscape discharge prediction because of the relative homogeneity in timing and duration of local wetland hydrologic connectivity in this landscape. We also show that this method will be transferable to other wetlandscapes, where individual storage elements respond hydrologically synchronously, whereas model performance is expected to deteriorate for hydrologically more heterogeneous wetlandscapes. Key Points: We extend a reduced‐complexity catchment model framework to wetlandscapes and demonstrate it for Big Cypress National Preserve, Florida Depth‐dependent extinction of evapotranspiration controls wetlandscape stage and discharge dynamics driven by hydroclimatic fluctuation Hydrological regime shifts between wet‐stagnant and wet‐flowing landscape states are explained by steady‐state stage stability analysis